System identification and PI control applied to refrigeration system for mango exportation - Manrique J. (2019)
In the northern region of Peru, the agro-export sector has grown considerably in the last ten years. In Piura specifically, it can be seen a huge expansion in products such as grape, mango and banana. Cooling systems are important for the agro-export sector representing between 40 and 50% of total electricity consumption, so it is necessary to have efficient automated cooling systems that would meet high quality and performance standards.In this article, a model based on transfer function has been identified for the refrigeration pilot plant of the University of Piura and a PI controller has been designed for said model, comparing its performance in relation to the ON OFF controllers currently used in the Peruvian agro-industry. The control variable was the compressor frequency and the controlled variable was the internal temperature of the cold-room.The refrigeration pilot plant of the University of Piura has the infrastructure of refrigeration systems used in Peruvian industry. The experiments were carried out for mango whose conservation temperature is 9° C. Settling time and overshoot were evaluated, between the PI controller and the traditional ON OFF control. The results show a stable temperature control with a dynamical response free of significant overshoot and zero offset between the process variable and the setpoint for steady state. © 2019 IEEE.